2022
DOI: 10.3389/fphar.2022.995481
|View full text |Cite
|
Sign up to set email alerts
|

Psychotropic drugs interaction with the lipid nanoparticle of COVID-19 mRNA therapeutics

Abstract: The messenger RNA (mRNA) vaccines for COVID-19, Pfizer-BioNTech and Moderna, were authorized in the US on an emergency basis in December of 2020. The rapid distribution of these therapeutics around the country and the world led to millions of people being vaccinated in a short time span, an action that decreased hospitalization and death but also heightened the concerns about adverse effects and drug-vaccine interactions. The COVID-19 mRNA vaccines are of particular interest as they form the vanguard of a rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 141 publications
0
4
0
Order By: Relevance
“… 21 For example, it was previously reported that individuals with severe psychiatric illness have lower counts of regulatory T cells and increased number of natural killer cells. 22 In addition, the anti-inflammatory and immunosuppressant action of psychotropic drugs may lower immune reactivity necessary for adequate vaccine response. 22 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 21 For example, it was previously reported that individuals with severe psychiatric illness have lower counts of regulatory T cells and increased number of natural killer cells. 22 In addition, the anti-inflammatory and immunosuppressant action of psychotropic drugs may lower immune reactivity necessary for adequate vaccine response. 22 …”
Section: Discussionmentioning
confidence: 99%
“… 22 In addition, the anti-inflammatory and immunosuppressant action of psychotropic drugs may lower immune reactivity necessary for adequate vaccine response. 22 …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we envision a near future when micro or nano grams of LNP-attached psychotropic drugs could be delivered to intra neuronal targets, averting systemic adverse effects. However, for that to happen, the LNP may need to be redesigned as some of the currently utilized lipids may interfere with the psychotropic drugs as we recently documented [49].…”
Section: Messenger Rna Vaccines a Short Overviewmentioning
confidence: 99%
“…In the endosome, ionizable lipids revert to their original positively charged state where they interact with anionic phospholipids to disrupt the endosomal membrane and facilitate release of intact mRNA-containing micelles into the cytoplasm. 6 , 7 Neutral phospholipids and cholesterol are responsible for maintaining an organized lipid shell. Helper lipids such as distearoylphosphatidylcholine (DSPC) also contribute to endosomal escape by interacting with the endosomal membrane.…”
Section: Introductionmentioning
confidence: 99%